2020
DOI: 10.1124/dmd.119.089656
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Proteomics of Clinically Relevant Drug-Metabolizing Enzymes and Drug Transporters and Their Intercorrelations in the Human Small Intestine

Abstract: The levels of drug-metabolizing enzymes (DMEs) and transporter proteins in the human intestine are pertinent to determine oral drug bioavailability. Despite the paucity of reports on such measurements, it is well recognized that these values are essential for translating in vitro data on drug metabolism and transport to predict drug disposition in gut wall. In the current study, clinically relevant DMEs [cytochrome P450 (P450) and uridine 59-diphospho-glucuronosyltransferase (UGT)] and drug transporters were q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(130 citation statements)
references
References 62 publications
5
124
1
Order By: Relevance
“…The final version may differ from this version. mass spectrometry-based quantitative proteomics studies of human liver and intestine (Couto et al, 2019(Couto et al, , 2020. A similarly high interbatch variability is seen across the two independent replicates of LabSkin.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The final version may differ from this version. mass spectrometry-based quantitative proteomics studies of human liver and intestine (Couto et al, 2019(Couto et al, , 2020. A similarly high interbatch variability is seen across the two independent replicates of LabSkin.…”
Section: Discussionmentioning
confidence: 85%
“…Although several artificial human skin models have been proposed, they are limited by a lack of understanding of xenobiotic metabolism and transport in human skin. Efforts have been made to understand XME gene expression in human skin and in vitro skin models using reverse transcription polymerase chain reaction (Kazem et al, 2019); however, it is increasingly accepted that mRNA abundance is a poor proxy for protein abundance and activity (Maier et al, 2009;Couto et al, 2020). In this study, we used a combination of label-free quantitative mass spectrometry and substrate-based mass spectrometry imaging to assess xenobiotic metabolism in human skin and an in vitro artificial skin model (LabSkin) and have quantified several XMEs for the first time in these systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Nadolol has been found to be a substrate of OATP1A2, and green tea catechins such as EGCG potently inhibit OATP1A2-mediated nadolol uptake. 6,8,9 Based on the assumption that OATP1A2 plays a role in the absorptive transport of nadolol in intestine, 14,15 it is suggested that the inhibition of OATP1A2 by catechins could lead to a reduction of intestinal absorption of nadolol. To gain insight into the effects of green tea on nadolol pharmacokinetics, the extent of green tea-nadolol interaction as indexed by % decrease in AUC of nadolol was plotted against estimated oral dose of EGCG in the different studies.…”
Section: Resultsmentioning
confidence: 99%